Prolactinoma as the cause of visual alterations in a female adolescent (2018)
Introduction: prolactinomas account for half of the etiological causes of presentation adenomas in the pediatric population, hence their important role as differential diagnosis in the study of a pituitary tumor. Visual alterations are not their most common symptom, but they should be borne in mind, particularly in the identification of a macroadenoma. Case presentation: female 16-year-old patient with a macroadenoma under study which was identified as a macroprolactinoma. The main symptoms at presentation were visual alterations and headaches. She received medical treatment with cabergoline at the Pediatric Endocrinology service, achieving stability in the size and characteristics of the tumor mass, and a reduction in serum prolactin levels. Conclusions: in the pediatric population, prolactinomas causing visual alterations are more common in males, but they can also occur among females. Their diagnosis includes specialized laboratory tests and neuroimaging, as well as the active involvement of the Pediatric Endocrinology service. Mention must be made of the medical treatment with dopaminergic agonists as the first choice for this condition before indicating surgery, and careful medical follow-up is required in this respect. © 2018, Editorial Ciencias Medicas. All rights reserved.